Virginia Woolf's "Mrs. Dalloway": a journey into the inner mind - Anievas Gamallo, Isabel Carmen (Estudios Humanísticos. Filología, 1992)
Virginia Woolf s Mrs. Dalloway is a work whose main subject matter is a journey into the private inner mind of different characters, and therefore, it can respond to what is generally understood by Stream-of-Consciousness fiction, since its "action" is more "mental" than actually "physical", and it takes place, mainly, in the pre-speech levels of consciousness. We know, however, that this kind of fiction needed a new form in which to be conveyed, "a very new sort of novelistic shell", as Jeremy Hawthorne says. Thus, we have considered the different technical tools Virginia Woolf uses to try to depict this inner consciousness convincingly. In the External Presentation we saw how the inner thoughts of the characters were basically rendered by two main techniques: Omniscient Description and Indirect Interior Monologue. In the more complex Interna! one we examined the use of Free Association, the broken syntax and the introduction of rhetorical devices such as anaphora, anacoluthum and repetition which give that appearance of discontinuity and incoherente of the private inner mind. With the same purpose, that is, to attempt to make a convincing and seemingly real depiction of the way this inner mind works, Virginia Woolf uses Private Images and Symbolism a use which seems to illuminate the theory that the making of symbols is a primary mental process. After considering briefly the question of the unity and organization of the work we tried to draw some conclusions about the actual aim of the journey: are we dealing with a truthful representation of the actual inner consciousness or with a deliberate artistic device to recreate it in fiction